2010
DOI: 10.1097/sla.0b013e3181f244f8
|View full text |Cite
|
Sign up to set email alerts
|

A Statewide Assessment of Surgical Site Infection Following Colectomy

Abstract: Objective-To determine the utility of adding oral non-absorbable antibiotics to the bowel prep prior to elective colon surgery Summary background data-Bowel preparation prior to colectomy remains controversial. We hypothesized that mechanical bowel preparation with oral antibiotics (compared to without) was associated with lower rates of SSI. Methods-24Michigan hospitals participated in the Michigan Surgical Quality CollaborativeColectomy Best Practices Project. Standard peri-operative data, bowel preparation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(81 citation statements)
references
References 26 publications
1
79
0
1
Order By: Relevance
“…Oral antibiotics were associated with a decreased SSI rate and this finding was corroborated by a meta-analysis of 13 other trials demonstrating that oral antibiotic use was associated with decreased SSI. Most recently, evaluation of the Michigan Surgical Quality Collaborative (MSQC) data (NSQIP methodology) using a propensity matched analysis found that patients who received oral antibiotics and mechanical bowel preparation as compared to those receiving mechanical bowel preparation alone had a lower rate of superficial and organ space infections [ 31 ]. Similar results were found with analysis of the Veterans Affairs Hospital data.…”
Section: Mechanical Bowel Preparation With Oral Antibiotics For Colorsupporting
confidence: 75%
“…Oral antibiotics were associated with a decreased SSI rate and this finding was corroborated by a meta-analysis of 13 other trials demonstrating that oral antibiotic use was associated with decreased SSI. Most recently, evaluation of the Michigan Surgical Quality Collaborative (MSQC) data (NSQIP methodology) using a propensity matched analysis found that patients who received oral antibiotics and mechanical bowel preparation as compared to those receiving mechanical bowel preparation alone had a lower rate of superficial and organ space infections [ 31 ]. Similar results were found with analysis of the Veterans Affairs Hospital data.…”
Section: Mechanical Bowel Preparation With Oral Antibiotics For Colorsupporting
confidence: 75%
“…After assessment of full‐text articles of the remaining 43 studies, 18 studies were excluded owing to the lack of MBP, prolonged courses of preoperative oral antibiotics, or the inclusion of patients undergoing emergency or urgent surgery. A further three studies were excluded as they were duplicate publications using cohorts already included in the meta‐analysis11, 12, 13. The remaining 22 studies were included in the review, of which 14 were RCTs14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, and eight were observational cohorts2 4, 28, 29, 30, 31, 32, 33 ( Table 1; Table   S1, supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, many trials show the benefit of adding oral antibiotics to mechanical bowl preparation to prepare their patients for gastrointestinal surgery in order to prevent infections and anastomotic leak. Most surgeons in the recent past did not routinely follow this concept [6,7].…”
Section: » Perioperative Sdd Should Be Considered For Patients Undergmentioning
confidence: 99%